Prediction of soil structure parameters dependent of physical properties at different soil management and texture - Dakhil R. Nedewi (University of Thi-Qar Journal of agricultural research, 2022)
This study was an attempt to predict the value of some soil structure parameters of MWD and WSA% as a function of soil content ( organic matter , total porosity, sand silt, clay) at different of soil management and soil texture. Six soil samples of the depth 0-30 cm were selected from three sites that different in texture of Clay, loam and Sandy loam in Basra Governorate (Abi Al-Khasib, Madinah and Zubair). Three samples represented the treatment of soil management (soil cultivated with alfalfa crop for 7 years respectively), and the other three samples from the same sites for uncultivated soil (bare soil) with three replicates for each sample. Soil organic matter content, total porosity , mean weight diameter, water aggregate stability percentage and particle size distribution were measured. The results showed that the MWD and WSA% as a function of some soil constituents( organic matter, total porosity, clay, silt and sand ) was represented by a highly significant linear equations. The correlation coefficients were highly significant and positive for all the studied constituent except for the sand, which it was negative.The results also showed that the change in the WSA% was greater compared with the MWD value depending at the changing of soil constituents. This is reflected in the increasing ​​of the regression constants of the linear equations.The results show that the highest values ​​of soil structural parameters were in the soil management treatment (cultivated soil) and increasing of clay and silt. The variation of the effect of soil constituent on both MWD and WSA% by using the linear correlation equation, The constituent were entered as independent variables to predict these two parameters in multiple linear correlation equations for soil constituents at a probability level of 1%.As this led to a very large increase in the values ​​of the correlation coefficient, which indicates the possibility of using multiple correlation equations for the constituents of the study soil to predict the values ​​of structural parameters.____________________________________________________________Keywords: soil management, mean weight diameter, water stability aggregate.